Incorporating resilience engineering into simulation for health care education and training. Issue 1 (March 2023) - Patterson, Emily S.; Winner, Jennifer; Patterson, Mary D.; Rayo, Michael F.; Deutsch, Ellen S
In this panel, we present perspectives on how to incorporate fundamental concepts in resilience engineering into health care human-in-the-loop simulations. Our panelists have successfully implemented concepts, but also continue to experience challenges with convincing colleagues of the importance and value of doing so for simulations that have other training, technology evaluation, or quality improvement objectives.